Weather effects on maize yields in Croatia in 2010 and 2011 - Kovačević Vlado; Rastija Mirta; Brkić Josip; Iljkić Dario (Agroznanje, 2012)
Maize is the main field crop on arable lands in Croatia. According to the data of Croatian Bureau of Statistics, maize was grown on 303300 ha/year in Croatia throughout 2001-2010 and annual yields ranged from 4.2 to 8.0 t/ha. Weather characteristics, especially precipitation quantities and their distribution, as well as mean air-temperatures are main reasons for considerable variation of annual yields of maize. The aim of this study was to test precipitation and temperature regimes with aspects of their favourability for maize growing during two growing seasons (2010 and 2011) based on six sites (Osijek, Slavonski Brod, Bjelovar, Sisak, Zagreb i Varaždin) data. The 2010 growing season was mainly favourable for maize growing and annual yield of maize in Croatia was 7.0 t/ha. Precipitation in the April-May period of 2010 (means of six tested sites) amounted to 710 mm or 54% above LTM, while mean air temperature in the same period was 17.9o C or 1.0o C higher compared to LTM. However, the 2011 growing season was less favourable for maize growing due to drought and high air-temperatures. For example, precipitation in the April-May period of 2011 was 274 mm or around 40% bellow LTM, while the air-temperature was 19.2o C or 2.3o C higher than LTM. As a result of less favourable weather conditions, it is estimated that the maize yields in 2011 were between 15% and even up to 30% lower compared to the normal weather years with the emphasis that yield reduction was higher in the Eastern part of the region and on light textured soils. Application of adequate soil management practices (for example, conventional soil tillage instead of reduced soil tillage, ploughing in autumn including the application of higher fertilization rates, especially potassium) and use of more tolerant hybrids could alleviate drought stress in maize growing.